3D electromagnetic simulation of interconnect fault inspection based on magnetic field behavior - Soeung, S. (2013)
This paper presents the 3D electromagnetic simulation investigation of magnetic field behavior of faulty and fault free interconnects in Computer Simulation Technology (CST) Microwave Studio. The interconnects have been modeled in three conditions: short fault, open fault, and normal. The simulations of interconnect fault inspection have been performed on two different observations. First on the induced magnetic field intensity behavior where the conductive lines are excited by voltage ports. The induced magnetic field intensities are detected by virtual probes available in CST at the location of 3 mm above the lines. Second observation is on the changes of the induced voltages across the eddy current coil sensor. The interconnects are exposed to an alternating magnetic field generating secondary magnetic field. This field induces changes of voltage which are detected by eddy current sensor placed at 1.5 mm above the interconnects. The simulation results generated from both cases have shown that in the presence of the short faults on interconnect, the peak magnetic field intensity and induced voltage are higher compared to the normal or reference interconnect of 0.708 mV. Whereas, open or discontinuity faults on the lines induced lower magnetic field intensity and voltage compared to the normal lines voltage of 0.708 mV. Â© 2013 IEEE.